Utility of hemoglobin A1c to screen for impaired glucose tolerance - Ginting, Edy K.; Aditiawati, Aditiawati; Irfanuddin, Irfanuddin (Paediatrica Indonesiana, 2014)
Background Childhood obesity is associated with an increased likelihood for having impaired glucose tolerance, dyslipidemia, and diabetes. Hemoglobin Ale (HbAl c) h as emerged as a recommended diagnostic tool for identifying diabetes and persons at risk for the disease. This recommendation was based on data in adults, showing the relationship between HbAl C and the future development of diabetes . However, studies in the pediatric population have been limited and no stan dard values of HbAlc levels in children have been established. Objective To evaluate HbAlc as a test for impaired glucose tolerance in obese children and adolescents and to identify the optimal HbAlc thresh old level (cut off poin t). Methods We studied 65 obese and 4 overweight children (BMI 2:: + 2 SD for age and gender) aged 10-15 years in Palembang. All subjects underwent HbAlc and oral glucose tolerance tests. Results Nineteen out of 69 subjects (28%) had impaired glucose tolerance. Based on the receiver operating characteristic curve, the optimal cut off point of HbAlc related to impaired glucose tolerance as diagnosed by oral glucose tolerance test was found to be 5.25%, with 63% sensitivity and 64% specificity, 40% positive predictive value, and 82% negative predictive value. The area under the receiver operating ch aracteristic curve was O .68 7 (95%CI 0.541-0.833; P < 0.00 1). Conclusion A HbAlc cut off value of 5.25% may be used as a screening tool to identify children and adolescents with impaired glucose tolerance.